Metastatic renal cell carcinoma in the nasopharynx - Yavuz Atar; Ilhan Topaloglu; Deniz Ozcan (Wolters Kluwer Medknow Publications, 2013)
Metastatic renal cell carcinoma of the nasopharynx, nasal cavity, and paranasal sinuses can be misdiagnosed as primary malignant or benign diseases. A 33-year-old male attended our outpatient clinic complaining of difficulty breathing through the nose, bloody nasal discharge, postnasal drop, snoring, and discharge of phlegm. Endoscopic nasopharyngeal examination showed a vascularized nasopharyngeal mass. Under general anesthesia, multiple punch biopsies were taken from the nasopharynx. Pathologically, the tumor cells had clear cytoplasm and were arranged in a trabecular pattern lined by a layer of endothelial cells. After the initial pathological examination, the pathologist requested more information about the patient's clinical status. A careful history revealed that the patient had undergone left a nephrectomy for a kidney mass diagnosed as renal cell carcinoma 3 years earlier. Subsequently, nasopharyngeal metastatic renal cell carcinoma was diagnosed by immunohistochemical staining with CD10 and vimentin. Radiotherapy was recommended for treatment.